SEARCH ENGINE OPTIMIZATION, INTEGRATED MARKETING COMMUNICATION, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN - Nisa', Miftakhul Mukarromatun; Ikhram W., M. Abdi Dzil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The rise of technological advancement in the globalization era results in the significantly tight atmosphere of competition between marketers. This study aims to measure the influence of the SEO (Search Engine Optimization) variable on the Purchase Decision of Arkatama Digital Marketing Training, the influence of the Integrated Marketing Communication variable on the Purchase Decision of Arkatama Digital Marketing Training, and the influence of the Perceived Value variable on the Purchase Decision of the Arkatama Digital Marketing Training. The type of research used is explanatory research. The datas were collected by distributing questionnaires, with a total of 63 respondents. The data analysis tool in this study uses SmartPLS 3.3.9, with a Likert scale as an additional tool. The results of hypothesis testing indicate that there is a significant effect between the SEO (Search Engine Optimization) on the Purchase Decision,  insignificant influence between the Integrated Marketing Communication on the Purchasing Decision, as well as the existence of significant influence between the Perceived Value on the Purchase Decision.